Clinical outcomes for olfactory neuroblastoma - Nakazono, Akira; Motegi, Hiroaki; Suzuki, Masanobu; Nakamaru, Yuji; Yamaguchi, Shigeru; Ishi, Yukitomo; Kano, Satoshi; Tsushima, Nayuta; Honma, Aya; Suzuki, Takayoshi; Kimura, Shogo; Hamada, Seijiro; et al. (Frontiers in Oncology, 2024)
Background: Olfactory neuroblastoma (ONB) is a rare malignant tumor arising from the olfactory neuroepithelium. The standard of care for ONB is surgical resection; however, detailed treatment protocols vary by institution. Our treatment protocol consists of endoscopic skull base surgery (ESBS) for endoscopically resectable cases and induction chemotherapy followed by craniotomy combined with ESBS for locally advanced cases, with postoperative radiotherapy performed for all cases. Chemoradiotherapy (CRT) is performed in unresectable cases. In this study, we evaluate our treatment protocol and outcomes for ONB.Methods: A retrospective review of patients with ONB was conducted. Outcomes included survival outcomes and perioperative data.Results: Fifteen patients (53.6%) underwent ESBS, 12 (42.9%) underwent craniotomy combined with ESBS, and 1 (3.6%) received CRT. The 5-and 10-year overall survival rates for all patients were 92.9% and 82.5%, respectively, with a median follow-up period of 81 months. The 5-and 10year disease-free survival rates were 77.3% and 70.3%, respectively, and the 5-and 10-year local control rates were 88.2% and 80.2%, respectively. Patients undergoing ESBS demonstrated a significantly shorter operating time, period from operation to ambulation, hospitalization period, and less blood loss than those undergoing craniotomy combined with ESBS.Conclusions: Our treatment protocol was found to afford favorable outcomes. Patients who underwent endoscopic resection showed lower complication rates and better perioperative data than those who underwent craniotomy combined with ESBS. With appropriate case selection, ESBS is considered a useful approach for ONB.